Videos to study Interactions in AGEing (VIntAGE): A longitudinal, ecological and multimodal French corpus - Duboisdindien, Guillaume; Bolly, Catherine T. (Journal of Language and Aging Research, 2024)
The Videos to study Interactions in AGEing (VIntAGE) corpus aims to investigate the complex relationship between language, cognition, and aging, focusing on verbal and non-verbal pragmatic markers in older persons with mild cognitive impairment (MCI). This multimodal and longitudinal corpus incorporates an analysis of gestural and verbal markers in discourse, aligned with neurolinguistic models. It provides a rich dataset for analyzing how aging impacts communicative competence in individuals with MCI. The VIntAGE corpus comprises approximately 18 hours of video recordings from 36 face-to-face interviews conducted by a close acquaintance of each of the nine women, all over 75 years old. Five participants were selected for in-depth analysis due to significant changes in their cognitive status. The participants underwent a series of semi-structured interviews over 15 months. The data were processed using transcription tools (for verbal discourse) and annotation tools (for gestures) and then subjected to Principal Component Analyses to manage each individual's diverse dataset and discursive modalities. The corpus includes the annotation of 6,351 verbal pragmatic markers (VPMs) and 8,044 non-verbal pragmatic markers (NVPMs). The data reveal an average decrease in MoCA scores from 23/30 to 20/30 over one year, highlighting cognitive decline's effects on verbal and non-verbal communication.